Experience of solid waste leading countries - Архіпова, Г.І.; Галушка, Ю.О. (Proceedings of National Aviation University (archive), 2009)
It is examined foreign and ukrainian experience of using efficient methods which deal with solid waste. It is analyzed approaches of developing methods and techniques of the efficiency measurement in treating solid waste.